Synthesis and Activity of Tumor-Homing Peptide iRGD and Histone Deacetylase Inhibitor Valproic Acid Conjugate - Peng, Zheng-Hong (2014)
In this report, we present a concise strategy to prepare a conjugate of the tumor homing peptide iRGD and histone deacetylase inhibitor Valproic acid, VPA-GFLG-iRGD. The conjugate VPA-GFLG-iRGD and a mixture of VPA and GFLG-iRGD have shown similar cytotoxicity against DU-145 prostate cancer cells. However, the treatment of DU-145 cells with conjugate VPA-GFLG-iRGD resulted in a decreased percentage of cells in the G2 phase, whereas the exposure of a mixture of VPA and GFLG-iRGD led to an increased percentage of cells in the G2 phase. We also found that GFLG-iRGD possessed cytotoxicity at the tested concentrations.